Building Trust and Convenience: How Online Reviews, Ratings, and Ease of Use Drive Fashion Purchase Decisions - Sunarjo, Wenti Ayu; Siti Nurhayati; Faillah Salwa Adn; Danang Satrio; M. Sigit Taruna (International Journal of Management, Economic, Business and Accounting, 2026)
Purpose of the study — This study aims to analyze the influence of Online Customer Review (X1), Online Customer Rating (X2), and Perceived Ease of Use (X3) on Purchasing Decisions (Y) among Henea.id. Research method—The research method used is a quantitative approach with a survey technique on 100 respondents selected purposively. The data obtained were tested through normality tests, heteroscedasticity tests, multiple linear regression tests, partial tests (t), and simultaneous tests (F). Result— The results of the study indicate that the three independent variables have a positive and significant effect on purchasing decisions. Online customer reviews have been shown to increase consumer trust in products. Online customer ratings play an important role in providing an overview of product quality and credibility. Meanwhile, Perceived Ease of Use is a dominant factor that encourages consumer comfort in making bold transactions. Simultaneously, these three variables have a strong contribution to influencing consumer purchasing decisions. Conclusion— This study emphasizes the importance of the role of consumer reviews, rating systems, and perceived ease of use in forming purchasing decisions in the digital era. The practical implications of this study can be a reference for business actors in designing more effective digital marketing strategies.